2007
DOI: 10.1074/jbc.m610579200
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-specific Activation of Human Telomerase Reverses Transcriptase Promoter Activity by Activating Enhancer-binding Protein-2β in Human Lung Cancer Cells

Abstract: The up-regulated expression and telomerase activity of human telomerase reverse transcriptase (hTERT) are hallmarks of tumorigenesis. The hTERT promoter has been shown to promote hTERT gene expression selectively in tumor cells but not in normal cells. However, little is known about how tumor cells differentially activate hTERT transcription and induce telomerase activity. In this study, we identified activating enhancerbinding protein-2␤ (AP-2␤) as a novel transcription factor that specifically binds to and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
63
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(68 citation statements)
references
References 44 publications
2
63
1
Order By: Relevance
“…Only one study based on cDNA microarray demonstrated the high expression of AP-2β in lobular breast tumor samples compared to ductal carcinomas [20]. Combined with the previous reports indicating AP-2β functionalized as oncogene to activate human telomerase reverses transcriptase and to up-regulate the transcription of the CRYAB gene through stabilizing p53 [21,22], most likely, we hypothesize the similarly tumorigenic role of AP-2β in breast cancer development, especially in advanced breast cancer.…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…Only one study based on cDNA microarray demonstrated the high expression of AP-2β in lobular breast tumor samples compared to ductal carcinomas [20]. Combined with the previous reports indicating AP-2β functionalized as oncogene to activate human telomerase reverses transcriptase and to up-regulate the transcription of the CRYAB gene through stabilizing p53 [21,22], most likely, we hypothesize the similarly tumorigenic role of AP-2β in breast cancer development, especially in advanced breast cancer.…”
Section: Introductionmentioning
confidence: 60%
“…However, to date, most studies focused on AP-2α and AP-2γ, and the reports about the other three family members, AP-2β, AP-2δ, and AP-2ε, were very rare. Our previous studies demonstrated the tumorigenic role of AP-2β in lung cancer by transcriptionally regulating human telomerase reverses transcriptase [22]. To expand this point, it might also play the same role in other cancer types, including breast cancer.…”
Section: Discussionmentioning
confidence: 95%
“…This observation is largely attributed to several key transcription factors in tumor cells that can up-regulate hTERT transcription [29]. To identify these potentially critical unknown factors, we successfully established a screening system that combined a streptavidin-agarose pulldown assay and high throughput proteomics [30]. One of the proteins identified using this systematic approach was CDC5L, which was expressed in hTERT promoter probe-protein complexes in the nuclear protein fractions prepared from colon cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a large number of TFs are known to activate hTERT transcription such as Sp1, c-Myc, GRHL2 and AP2 [16][17][18][19][20][21][22]. Of these, c-Myc has been directly observed to interact with E-boxes and its activation of hTERT transcription is partly dependent on chromatin configuration of the hTERT gene [23,24].…”
Section: Introductionmentioning
confidence: 99%